Selective oxidation of cyclopentene catalyzed by Pd(CH3COO) 2-NPMoV under oxygen atmosphere - Sui, C.; Lu, G.; Li, Xin Yong; Qu, Z.; Zou, X.; Chen, G. (2008)
The selective oxidation of cyclopentene to cyclopentanone catalyzed by Pd(CH3COO)2-NPMoV was investigated under atmospheric oxygen in aqueous acetonitrile acidified by CH3SO3H. It was shown that the conversion of cyclopentene and the yield of cyclopentanone was nearly 100% and 94.6%, respectively, under the optimized reaction condition. © 2008 Springer Science+Business Media, LLC.